Pengaruh Vaksin Sinovac terhadap Siklus Menstruasi pada Remaja Perempuan Berbasis Studi Farmakovigilans di Banjarmasin Selatan: Effect of Sinovac Vaccine on Menstrual Cycle in Adolescent Girls Based on Pharmacovigilance Study in South Banjarmasin - Iwan Yuwindry; Muhammad Rifqi Dharmawan; Nailul Muna; Wanda Nisa Pratiwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The spread of the Coronavirus that causes the COVID-19 pandemic in the world has not subsided. Even recently, the Omicron variant has spread in many countries and caused a spike in cases. Meanwhile, cases of COVID-19 in Indonesia are also increasingly worrying. This can be seen from active cases and the death rate is still increasing. The commitment to seriously implement the health protocols as the first step in overcoming the COVID-19 pandemic must continue to be voiced and become a shared commitment. Protecting the people from the pandemic threat, including implementing a free vaccination program for the community, must be a priority for the country. When vaccination is started, it is possible that an unwanted reaction to the vaccine will occur, which is why this proposal was written. The incidence of unwanted drug reactions is related to Pharmacovigilance, a science and activity related to detecting, assessing, understanding, and preventing adverse effects.